Wikipedia: A Key Tool for Global Public Health Promotion - Heilman, James M; Kemmann, Eckhard; Bonert, Michael; Chatterjee, Anwesh; Ragar, Brent; Beards, Graham M; Iberri, David J; Harvey, Matthew; Thomas, Brendan; Stomp, Wouter; Martone, Michael F; Lodge, Daniel J; et al. (JMIR Publications, 2011)
The Internet has become an important health information resource for patients and the general public. Wikipedia, a collaboratively written Web-based encyclopedia, has become the dominant online reference work. It is usually among the top results of search engine queries, including when medical information is sought. Since April 2004, editors have formed a group called WikiProject Medicine to coordinate and discuss the English-language Wikipedia's medical content. This paper, written by members of the WikiProject Medicine, discusses the intricacies, strengths, and weaknesses of Wikipedia as a source of health information and compares it with other medical wikis. Medical professionals, their societies, patient groups, and institutions can help improve Wikipedia's health-related entries. Several examples of partnerships already show that there is enthusiasm to strengthen Wikipedia's biomedical content. Given its unique global reach, we believe its possibilities for use as a tool for worldwide health promotion are underestimated. We invite the medical community to join in editing Wikipedia, with the goal of providing people with free access to reliable, understandable, and up-to-date health information.